Numerical investigation of a water flow in a rib-roughened channel by using Reynolds stress model - Bayraktar, Seyfettin; Bayraktar, Meral; Vardar, Nurten (TAYLOR & FRANCIS LTD, 2008)
In this paper, water flow in a rib-roughened channel is investigated numerically by using Reynolds stress turbulence models (RSM) on a three-dimensional (3-D) domain. Computational results for mean streamwise velocity component and turbulent kinetic energy show good agreements with available experimental data. Five rib pitch-to-height ratios (p/h) of 1, 5, 10, 15 and 20 are analysed for six different Reynolds numbers (Re) of 3000, 7000, 12,000, 20,000, 40,000 and 65,000. Velocity vectors, streamlines and Reynolds stresses are showed for these ratios and Re numbers. Streamlines revealed that Reynolds numbers do not affect flowfield but play an important role in the Reynolds stresses.
Keywords: rib-roughened channel; Reynolds stress turbulence model; skin friction; computational fluid dynamics (CFD); water flow; TURBULENT HEAT-TRANSFER; EDDY SIMULATION; OPTIMIZATION; ROUGHNESS; SURFACE; RANS; Mechanics; Physics